Penggunaan Sistem Informasi Pencalonan (SILON) Pada Pemilihan Kepala Daerah Calon Perseorangan Tahun 2020 di Kabupaten Samosir - Silalahi, Chandra Gobles; Zulakarnain, Iskandar; Fauzan, Indra (PERSPEKTIF, 2024)
This research is motivated by the registration of candidacy through individual channels which are required to use access through the Candidacy Information System (SILON). However, there are still many obstacles in the system starting from the location of implementation such as in Samosir Regency with network conditions that have not been evenly stable and problems with the system. This research aims to explain how the use of the nomination information system at the stage of registration of candidates through individual channels in Samosir Regency and analyze what are the obstacles in using the system. This research method is descriptive qualitative which presents the facts found comprehensively with data collection techniques through interviews, documentation, and observation. The results showed that the Samosir Regency KPU has implemented a nomination information system in the 2020 Regional Head election for individual candidates in the Samosir Regency by the technical instructions and stages specified. However, the use and workings of the system have not been optimal to support the efficiency and principles of the KPU with frequent system changes and environmental conditions that have not been supportive. In every process of use, it is necessary to evaluate policies in the nomination information system.